ANTIHYPERURICEMIC EFFECT OF CLOVE LEAF (Syzygium aromaticum L.) ON DECREASING URIC ACID LEVELS IN BLOOD RAT (Rattus norvegicus) - Laratmase, Nia; Nindatu, Maria (Universitas Pattimura, 2019)
This research is laboratory experimental in nature and was analyzed using Analysis of Variance and continued with Duncan's test, with 95% confidence (α=0.05) using SAS software. The results showed that giving clove leaf steeping could reduce uric acid levels in the blood of Rattus norvegicus rats. Clove leaf infusion (Syzygium aromaticum L.) contains flavonoids which have xanthine oxidase inhibitory activity, including luteolin, apigenin, kaemferol, and quercetin. In addition, Vitamin C can reduce oxidative stress and inflammation which affect the decrease in uric acid synthesis. Other compounds, namely tannins, alkaloids, and saponins have the same role as flavonoids, namely reducing the activity of the enzyme xanthine oxidase in serum and increasing the concentration of uric acid in the urine, as well as binding free radicals during the conversion of purines into uric acid. Infusion of clove leaves doses of 0.09g, 0.18g and 0.36g can reduce uric acid levels in the blood of rats (Rattus norvegicus) with an effective dose of 0.36g.